Optimation of feed distributing component of a mechanical bottom feeder prototype. - Nuevaspaña, Jover S. (Miagao, Iloilo College of Fisheries, University of the Philippines, 2012)
Aquaculture is a growing industry with a large contribution to the country's total fish demand. Technological development was utilized to further increase the production in ponds and cages. Such development includes the use of automated feeding system to save time, minimize feed wastage and cut labour expenses. Automatic feeders can be classified according to their energy supply as being electric, pneumatic and hydraulic-type feeders. Hydraulic-type feeder can be used to disperse the feeds electric, bottom of cage to make it more accessible to the fish. Feed dispersion rate is affected by factors such as volume of water entering the feed distributing component, impulse regenerated inside the inlet pipe and velocity and flow rate of the water entering the pipe. The dispersion rate can be optimized by decreasing the volume of water entering the inlet pipe holes but not to the point that the bubbles could also be dispersed along with feeds. These bubbles could scare the fishes away from the feeder thus defeating its purpose of increasing feed accessibility. Ideally, the mechanical bottom feeder should have a high rate for it to distribute a ration in a short period of time interval, especially in the intensive culture systems where the feed ration is high. This bottom feeder can be implemented in cage culture systems.
Keywords: Aquaculture--College of Fisheries, UPVisayas